Growth of CNT Forests on Titanium Based Layers, Detailed Study of Catalysts - Szabó, Anna; Andricević, Pavao; Pápa, Zsuzsanna; Gyulavári, Tamás; Németh, Krisztián; Horvath, Endre; Forró, László; Hernadi, Klara (Frontiers in Chemistry, 2018)
For better electrical contacts of potential devices, growth of vertically aligned carbon nanotubes (CNT forests) directly onto conductive substrates is an emerging challenge. Here, we report a systematic study on the CCVD synthesis of carbon nanotube forests on titanium based substrates. As a crucial issue, the effect of the presence of an insulating layer (alumina) on the growing forest was investigated. Other important parameters, such as the influence of water vapor or the Fe-Co catalyst ratio, were also studied during the synthesis. As-prepared CNT forests were characterized by various techniques: scanning and transmission electron microscopies, Raman spectroscopy, spectroscopic ellipsometry. CNT forests grown directly onto the conductive substrate were also tested as electrodes in hybrid halide perovskite photodetectors and found to be effective in detecting light of intensity as low as 3 nW.